Strategi Sekolah Mengatasi Prilaku Tidak Disiplin Siswa di SD Negeri 138 Palembang - Alimin; Muhamad Idris; Melinda Puspita Sari Jaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the school's strategies in addressing students' indiscipline at SD Negeri 138 Palembang. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings indicate that the school applies preventive strategies by emphasizing character education through learning approaches such as project-based activities, classroom agreements, and instilling values like responsibility, cooperation, and independence. Parental involvement also plays an important role in supporting students’ discipline through consistent communication and collaboration at home. However, the implementation of these strategies faces several challenges, including limited teacher understanding of character-based learning, lack of supporting facilities, and low parental participation. Therefore, stronger collaboration among teachers, parents, and school administrators is needed to ensure that student discipline strategies can be carried out effectively and sustainably